Contingency for Novel Diagnosis and Therapies for Hirschsprung’s Disease - Dongare, Sayali Arun; Bastapure, Rutuja Sunil; Lohiya, Gopal Vijaykumar; Satpute, Kranti Limbajirao (Indian Journal of Pharmacy Practice)
The majority of frequent reason of low functional blockage of the bowel in pediatrics is a Hirschsprung disease, which is brought on by a genetic mutation that disrupts the enteric nerve system. The absence of enteric ganglia over a varied length of intestine characterizes this developmental condition, which is classified as a neurocristopathy. Hirschsprung disease is a complicated surgical and medical condition that seems to have different social and health consequences based on the age of the patient and level of neurodevelopment. This review examines the genetic variables that influence development of Hirschsprung disease as well as its prevalence and congenital connection. An overview of a Hirschsprung's disease and its etiology, diagnosis, course of therapy are the goals of this article.
Keywords: Complication; Diagnosis; Etiology; Hirschsprung’s disease; Management of disease and Ayurvedic treatment